Multiplex RT-PCR Assay for Crinivirus Detection Using RNA Prepared from Three Extraction Methods on Tomato Plant - Esti Prasetya Ningrum; Sedyo Hartono; Sri Sulandari; Susamto Somowiyarjo (Universitas Gadjah Mada, 2019)
Tomato infectious chlorosis virus (TICV) and Tomato chlorosis virus (ToCV) are members of the Crinivirus genus that induces yellowing symptoms in tomato plants. Detection of both viruses is generally carried out singly, thus it is necessary to develop a fast, accurate and efficient detection method to detect multiple viruses simultaneously in an effort to determine the suitable disease management strategies. This study was aimed to detect both viruses using the multiplex RT-PCR method and evaluate three methods of total RNA preparation used from tomato plants as RT-PCR templates. The methods evaluated were simple direct tube (SDT), simple dsRNA, and commercial kit (RNeasy Plant Mini Kit) as a comparison. The total source of RNA came from Crinivirus symptomatic tomato leaves from Kopeng, and Ketep (Central Java); Pakem (Yogyakarta); Malang (East Java); and Bogor (West Java). Single RT-PCR and multiplex RT-PCR using specific primers CPd I/CPd II and ToCV CF/ToCV CR with DNA band targets of 760 bp and 360 bp. The SDT and dsRNA methods have been successful in obtaining total RNA and viral RNA from tomato leaf samples. Total RNA RT-PCR with simple SDT and dsRNA methods followed by multiplex RT-PCR produces specific DNA band intensities that are comparable to Kit. RNA preparation with SDT and simple dsRNA methods is a simple, fast, easy and affordable method in providing templates for RT-PCR. Multiplex RT-PCR technique using two pairs of specific primers CPd I/CPd II and ToCV CF/ToCV CR is suitable for simultaneous testing of TICV and ToCV.